Synthesis and characterization of gold and gold-cuprous oxide nanostructures - Gul Naz, 1977- , author 608976; Zulkafli Othaman, 604300 supervisor; Mustaffa Shamsuddin supervisor 189976; Fakulti Sains 8004 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D (Fizik)) - Universiti Teknologi Malaysia, 2017